2012
DOI: 10.1111/j.1365-294x.2012.05541.x
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting changes in population genetic structure of alpine plants in response to global warming

Abstract: Species range shifts in response to climate and land use change are commonly forecasted with species distribution models based on species occurrence or abundance data. Although appealing, these models ignore the genetic structure of species, and the fact that different populations might respond in different ways because of adaptation to their environment. Here, we introduced ancestry distribution models, that is, statistical models of the spatial distribution of ancestry proportions, for forecasting intra-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 83 publications
2
145
0
1
Order By: Relevance
“…The changes in the genetic diversity patterns of these circumboreal plants depended on the type of molecular marker and patterns of genetic diversity distribution. This fact was also supported in a few other surveys, i.e., Collevatti et al (2011), Alsos et al (2012, Jay et al (2012), and Temunovic et al (2013). In the case of circumboreal plants, the expected future loss of geographic range was not necessary accompanied by a marked reduction of genetic diversity, but it has a strong effect on allelic richness, even if genetic diversity was quite uniformly distributed.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…The changes in the genetic diversity patterns of these circumboreal plants depended on the type of molecular marker and patterns of genetic diversity distribution. This fact was also supported in a few other surveys, i.e., Collevatti et al (2011), Alsos et al (2012, Jay et al (2012), and Temunovic et al (2013). In the case of circumboreal plants, the expected future loss of geographic range was not necessary accompanied by a marked reduction of genetic diversity, but it has a strong effect on allelic richness, even if genetic diversity was quite uniformly distributed.…”
Section: Discussionsupporting
confidence: 50%
“…The homogeneity of the genetic background-the lack of admixture and the domination of one gene pool in most populations throughout the ranges of these two plants-becomes more pronounced in the future. In this case, the ancestry distribution model combined with geographic distribution of populations and environmental data (Jay et al 2012) assumes gene flow as the main component in the response of plant populations to environmental modifications and favors migration toward similar environments. Therefore, this model showed that resident genes can move to suitable places in a way that conserves the realized niche of a given genetic cluster.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations